Inovasi Reaktor Pirolisis Sampah Plastik Campuran Sampah Perkotaan Dengan Tabung Mendatar Dan Kondensor Bertingkat Kapasitas 50 Kg Self-Sufficient - Sutisna, Utis; Sugiantoro, Bambang; Soleh, Muhamad; Martuti, Nana Kariada Tri; Widowati, Widowati; Sunyoto, Sunyoto (PPPM POLTESA, 2024)
The management of urban plastic waste poses a significant challenge for the global environment and economy. An innovative horizontal tube pyrolysis reactor with a tiered condensation system, designed for a capacity of 50 kg, has been developed to convert mixed plastic waste into liquid fuels such as diesel, kerosene, and gasoline through an efficient and environmentally friendly pyrolysis process. The reactor, with a diameter of 760 mm and a length of 1200 mm, maximizes heat distribution to ensure uniform heating without requiring mechanical rotation or stirring. External heating is maintained at a temperature range of 300°C to 350°C under anaerobic conditions to prevent direct combustion. System trials demonstrated that the conversion of plastic waste to liquid fuel products can achieve an efficiency of up to 70% of the total input mass, yielding an average of 50% liquid fuel fractions, 15% solid residue, and 35% pyrolysis gas. Analysis of the liquid fuel quality indicates hydrocarbon content comparable to conventional fuels, with potential applications in internal combustion engines. The system is designed to be self-sufficient, utilizing pyrolysis gas to sustain the process and thereby reducing external energy requirements by up to 30%. These findings highlight the significant potential of horizontal tube-based pyrolysis systems in efficiently reducing urban plastic waste while providing alternative fuel sources. This technology can thus support sustainable waste management efforts and contribute to the transition toward renewable energy.